2005
DOI: 10.1121/1.1903845
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of decay times in coupled spaces: Reliability analysis of Bayeisan decay time estimation

Abstract: This paper discusses quantitative tools to evaluate the reliability of "decay time estimates" and inter-relationships between multiple decay times for estimates made within a Bayesian framework. Previous works [Xiang and Goggans, J. Acoust. Soc. Am. 110, 1415-1424 (2001); 113, 2685-2697 (2003)] have applied Bayesian framework to cope with the demanding tasks in estimating multiple decay times from Schroeder decay functions measured in acoustically coupled spaces. A parametric model of Schroeder decay function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
0
35
0
1
Order By: Relevance
“…In the physical world, impedance effects at the boundary and considerations of wavelength compared to opening size could reduce the decay ratio values, so that the high values of decay ratio predicted theoretically would be invalid. Furthermore, high decay ratios are usually accompanied by higher uncertainty values in the Bayesian analysis, as explained by Xiang et al 20 Although the decay ratio and ⌬dB results from theory and from Bayesian analysis of the computer modeled impulse responses do not perfectly match, it is still of interest to use the simulated results to learn more about the subjective perception of DSE.…”
Section: B Decay Ratio and ⌬Db Resultsmentioning
confidence: 93%
“…In the physical world, impedance effects at the boundary and considerations of wavelength compared to opening size could reduce the decay ratio values, so that the high values of decay ratio predicted theoretically would be invalid. Furthermore, high decay ratios are usually accompanied by higher uncertainty values in the Bayesian analysis, as explained by Xiang et al 20 Although the decay ratio and ⌬dB results from theory and from Bayesian analysis of the computer modeled impulse responses do not perfectly match, it is still of interest to use the simulated results to learn more about the subjective perception of DSE.…”
Section: B Decay Ratio and ⌬Db Resultsmentioning
confidence: 93%
“…Bradley and Wang 1 tested two quantifiers that can theoretically identify DSE profiles more uniquely: the decay ratio ͑T 2 / T 1 ͒ and ⌬L. ⌬L is defined as the difference in decibels between the two y-intercepts in the DSE profile ͑referred to as ⌬dB in previous studies͒, calculated from data produced by a Bayesian analysis algorithm developed by Xiang et al 5,6,16 In this investigation, decay ratio and ⌬L showed trends similar to T30/T15, except for cases with the largest coupled volume size in which the results were harder to interpret. 1 In another study, Bradley and Wang 17 analyzed computational models of an existing coupled volume concert hall, and compared the DSE quantifiers listed above as well as a newly proposed quantifier, late decay time/early decay time ͑LDT/EDT͒.…”
Section: Previous Researchmentioning
confidence: 99%
“…The application of Bayesian inference in the acoustics of coupled rooms has been well documented in a series of papers by Xiang and Goggans [6]- [8] and Goggans et al [9]. Figure 2(A) and Figure 2(B) show plots of the likelihood function for the decay models of decay order two and one respectively which are denoted by H 1 and H 2 , the boundary of the plots also define the range of a normalized prior π(x|H i ) used in each calculation.…”
Section: Example: Determining the Order Of Decay Times In Acousticallmentioning
confidence: 98%